Mega project : KFC Holdings (Malaysia) Berhad / Azhar Abu Bakar, Azlinda Ahmad and Norazlina Mohsin - Abu Bakar, Azhar; Ahmad, Azlinda; Mohsin, Norazlina (Faculty of Business and Management, 2001)
KFC (Kentucky Fried Chicken) Holdings (Malaysia) Bhd ("KFCH") commands a dominant position in Malaysia's dynamically expanding retail food industry. Since the first Kentucky Fried Chicken outlet opened its doors to a receptive Malaysian public in 1973, the Group has developed its operations in both breadth and depth and has evolved into a fully integrated food operator. Its operations, comprising 2 major internationally renowned fast-food chains, local chicken retail chain, integrated poultry operations and ancillary operations, are uniquely structured to enhance its range of business activities, efficiencies and profitability. Being Malaysia's only integrated food operator, KFCH is involved in a highly profitable and fast growing food and food processing business. This includes a feedmill, breeder farms, hatchery, contract broilers farms, poultry processing plants, further processing plants, sauce manufacturing, bakery, commissary and industrial and institutional catering. KFCH was incorporated in Malaysia under the Companies Act, 1965 on 22 December 1980 as a private limited company under the name of Poon Guan Holdings Sdn Bhd. The Company adopted its present name on 11 July 1986 and was converted to a public company on 13 March 1987. The Company was listed on the Main Board (Consumer Product) of the KLSE on 11 November 1988.